HUBUNGAN ANTARA TINGKAT KECANDUAN INTERNET DENGAN HASIL PRESTASI BELAJAR MAHASISWA DI PERGURUAN TINGGI SWASTA KESEHATAN DI YOGYAKARTA - Petra Bella Debora Christie; Yulia Wardani; Chistina Ririn Widianti (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2021)
The internet is very useful in supporting learning process in the pandemic time yet has negative effect which is addiction. Internet addiction has an impact on mental health and a potency to influence the future. The purpose of this study was to determine the significant relationship between internet addiction level and student learning achievement. Using descriptive correlative, cross sectional approach to 103 respondents amd Somers'd Correlation Test. The results of the study showed that the109 (36.2%) respondents had mild level of internet addiction, 28 (9.3%) moderate and 4 (1.3%) were mild. The academic achievement of 172 (57.1%) respondents were in highly satisfactory, non-academic achievements of more than half 224 (81.1%) very poor. There was no significant relationship between internet addiction level and academic learning achievement results with a score of r = -0.17 and p value = 0.753. There is a significant association between internet addiction rates and non-academic learning achievement results with a score of r = 0.193 and p value = 0.000. The students are push to improve non-academic achievement and avoid internet addiction. Keywords: internet addiction level, academic learning achievement, non academic learning achievement.